Perspectives of compounding pharmacists on alcohol-based hand sanitizer production and utilization for COVID-19 prevention in Addis Ababa, Ethiopia: A descriptive phenomenology study - Baye, Assefa Mulu (PLoS One, 2021)
BACKGROUND: Globally, the safety of patients and healthcare providers is at risk due to health care-associated infections (HCAIs). World Health Organization and the Centers for Disease Control and Prevention recommend using alcohol-based hand rub (ABHR) for hand hygiene in healthcare settings to prevent HCAIs. Irrational use of ABHR will have undesirable consequences including wastage of products, exposure of healthcare providers to infections and emergence of microbial resistance to the alcohol in hand sanitizers. This study aimed to explore the perspective and experiences of compounding pharmacists on production and utilization of ABHR solution for coronavirus disease in 2019 (COVID-19) prevention in public hospitals of Addis Ababa, Ethiopia. METHODS: A descriptive qualitative study using in-depth interview of 13 key-informants serving as compounding pharmacists in public hospitals of Addis Ababa, Ethiopia, was conducted. The study participants were identified and selected by purposive sampling. All transcribed interviews were subjected to thematic analysis and transcripts were analyzed manually. FINDINGS: The compounding pharmacists in this study had a mean age of 30.6 (±3.1) years and nine of the thirteen participants were men. Ten participants believed that the compounding practice in their respective sites followed the principles of good compounding practice. More than half of the participants did not believe that ABHR products were used rationally in health facilities. They argued that users did not have enough awareness when and how to use sanitizers. Most of the interviewees reported that compounding personnel had no formal training on ABHR solution production. Study participants suggested incentive mechanisms and reimbursements for experts involved in the compounding of ABHR solutions. CONCLUSION: Three of the compounding pharmacists indicated that ABHR production in their setting lack compliance to good compounding practice due to inadequate compounding room, quality control tests, manpower and equipment. Despite this, most study participants preferred the in-house ABHR products than the commercially available ones. Thus, training, regular monitoring and follow-up of the hospital compounding services can further build staff confidence.